Inventory Management of Health Commodities in a Tertiary Teaching Hospital in Ethiopia - Legese, Nanati; Teshome, Dawit; Gedif, Teferi (Frontiers in Pharmacology, 2022)
Analyzing purchased health commodities based on their budgetary consumption and importance is crucial for efficient utilization of a hospital’s budget. Therefore, the purpose of this study was to analyze a three years inventory of health commodities (medicines, medical supplies and laboratory reagents and chemicals) in Saint Paul Hospital Millennium Medical College (SPHMMC). Methodology The study was conducted in SPHMMC located in Addis Ababa, Ethiopia.. A three years data were collected and ABC, VEN and ABC-VEN matrix techniques were applied for the analysis. The data collection period was from March-April, 2017. Results An average of 296 medicines, 194 laboratory commodities and 105 medical supplies were purchased over three years. Class A medicines which consumed 80% of the total Annual pharmaceutical Expenditures (APE) account 17.8%-20% of the total medicines by quantity. Antibiotics (ceftriaxone 1gm injection, vancomycin 1g and metronidazole), I.V fluids (sodium chloride 0.9% injection and dextrose 40% injection) and anti-diabetic medication (insulin zin suspension and metformin) are among the top ten medications by value that consumed significant budget of the hospital. On ABC-VEN matrix analysis, a single expensive and non-essential medicine (valganciclovir HCL 450 mg tablet) consumed 9.4% of expenditure in 2014/15. There were laboratory commodities procured out of the VEN list, and these accounted for 6.8-31.2% of the total laboratory expenditures over the three years. Gauze surgical 90cmx100m, surgical glove sterile latex number 7.5 and examination glove were the top three based on expenditures in all the studied years. In 2015/16, examination glove alone consumed 71.9% of the total expenditure. Conclusion SPHMMC manages large numbers of health commodities which necessitate efficient inventory management practice in place. However, the purchase of the commodities particularly those products used for laboratory diagnosis is not strictly based on the hospital’s VEN list, indicating the need for better communication of laboratory unit with DTC of the hospital. The DTC of the hospital should update the VEN list of the health commodities and strictly enforce the hospital procurement to adhere the agreed list of medicines.